Significance of C-11 Methoxylation in desymmetrization of Cephalostatins - Mansour M. Nawasreh (Results in Chemistry)
Aiming on targeting cephalostatin 1, a potentially active anti-tumor marine natural product structured as a bis-steroidal pyrazine BSP, significant efforts invested to synthesize a closed structure. Herein, the effect of introducing α-configurated methoxy group at C-11 on the chemistry of symmetrical BSP system is under focus. The significance of directing various reagents either to the methoxy half or to the methoxy-free half of this complicated BSP is highlighted. Several nucleophilic additions as sodium borohydride reduction, carbonyl oximation, nucleophilic addition of hydrazine derivatives and the reaction with Wittig-ylid were directed specifically to the methoxy-free half. However, F-ring opening process as well as hydroboration of ring-D double bond was directed selectively toward the methoxy half. In both cases, these processes led to a chemoselective/specific product. Moreover, the development of a mild demethoxylation reaction to remove the methoxy group, whenever wanted, gives us more ability and flexibility in controlling successive reactions and hence to play in any part of the playground. Both methoxylation and demethoxylation of C-11 are novel approaches applied in the cephalostatin research area. Thus, building up of a multi-step synthetic strategy to achieve the targeted molecule is now more possible.